Rethinking the Roles of English Lecturers in the Digital Era - Disa Evawani Lestari (Metathesis: Journal of English Language, Literature, and Teaching, 2020)
Along the era of rapid technology advancement on the performance of Artificial IAlong with the era of rapid technology advancement on the performance of Artificial Intelligence (henceforth AI), there have been intense discussions and debates among educationists about the future of human teachers and AI teachers. When information can be accessed easily amidst the rapid development of online learning, it is intriguing to listen to students’ perspectives on the roles they expect from their teachers, especially in learning English subjects, when abundant resources are available and accessible online within their fingertips in social media platforms and online learning websites. In short, to identify what cannot be fulfilled online. To serve that purpose, 160 students from a private university in Indonesia were recruited as research participants. They are from 16 different study programs recruited as participants through a purposive sampling method to see if findings are bound to study program types. Data were collected through an online questionnaire and an interview. The results indicated that the students perceive their teachers as someone to guide their learning by providing good online resources and immediate feedback rather than expecting their teachers to be a content expert or to have a linguistic performance like native teachers.